1998
DOI: 10.1159/000029039
|View full text |Cite
|
Sign up to set email alerts
|

Ethological Remarks on Mannerisms

Abstract: Mannerisms are symptoms of various psychiatric disorders. The term has not been defined thoroughly and is often confused with stereotypies or the more generally used term ‘bizarreness’. From an ethological perspective, mannerisms may be regarded as pathologically altered forms of ritualised behaviour that serve a communicative purpose. Mannerisms are maladaptive behaviours since they lead to withdrawal of and rejection by the socially interacting partner, or even induce aggressive behaviour due to the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
290
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(305 citation statements)
references
References 18 publications
14
290
1
Order By: Relevance
“…The harmonic approximation should only be expected to work well at sufficiently low temperatures, where all modes can be considered harmonic (excluding possible quantum effects at very low temperatures), but several studies have shown that it is often applicable even at rather high temperatures 19,20 and in highly complex systems. 21 The quantum nature of the hydrogen atoms must also be considered.…”
Section: A Transition State Theorymentioning
confidence: 99%
“…The harmonic approximation should only be expected to work well at sufficiently low temperatures, where all modes can be considered harmonic (excluding possible quantum effects at very low temperatures), but several studies have shown that it is often applicable even at rather high temperatures 19,20 and in highly complex systems. 21 The quantum nature of the hydrogen atoms must also be considered.…”
Section: A Transition State Theorymentioning
confidence: 99%
“…To construct such small particles we have exploited the epitaxial growth of Co on Pt(111) in ultra-high-vacuum (UHV), which allows us to obtain a narrow size distribution by means of kinetically controlled growth [23]. This technique exploits the energetic hierarchy of the different diffusion and dissociation processes of adatoms at surfaces, and their dependence on the substrate symmetry.…”
Section: Orbital Magnetic Moment and Magnetic Anisotropy Of Single Comentioning
confidence: 99%
“…This technique exploits the energetic hierarchy of the different diffusion and dissociation processes of adatoms at surfaces, and their dependence on the substrate symmetry. Control is achieved by means of external parameters such as, e.g., the substrate temperature and deposition flux, allowing atoms to diffuse and nucleate forming aggregates of defined size and shape [23]. The Co/Pt system was chosen in order to maximize the MAE effects, since hcp-Co presents the largest MAE among 3d ferromagnetic elements (0.045 meV/atom compared to, e.g., 0.005 meV/atom for Fe).…”
Section: Orbital Magnetic Moment and Magnetic Anisotropy Of Single Comentioning
confidence: 99%
See 1 more Smart Citation
“…Strain-relief patterns formed by heteroepitaxial films act as templates for the self-assembly of highly ordered nanostructure superlattices. 1 The first system where the growth kinetics has been studied is a superlattice of Ag islands grown on a trigonal network (TN) formed by two monolayers (ML) of Ag/Pt(111). 2,3 The system has been modeled by assuming a network of surface Shockley partial dislocations 4 acting as repulsive line defects and thus confining the deposited Ag adatoms into the (25 × 25) unit cells.…”
mentioning
confidence: 99%